Advanced Computational Pipeline for FAK Inhibitor Discovery: Combining Multiple Docking Methods with MD and QSAR for Cancer Therapy - Pinar Siyah (Computation)
Synthetic lethality, involving the simultaneous deactivation of two genes, disrupts cellular functions or induces cell death. This study examines its role in cancer, focusing on focal adhesion kinase and Neurofibromin 2. Inhibiting FAK, crucial for synthetic lethality with NF2/Merlin, offers significant cancer treatment potential. No FAK inhibitor has been clinically approved, underscoring the need for new, effective inhibitors. The small-molecule FAK inhibitors identified in this study show promise, with SP docking, IFD, QPLD, and MD simulations revealing intricate interactions. Based on the comprehensive analysis, the MM/GBSA scores from SP docking for amprenavir, bosutinib, ferric derisomaltose, flavin adenine dinucleotide, lactulose, and tafluprost were determined as −72.81, −71.84, −76.70, −69.09, −74.86, and −65.77 kcal/mol, respectively. The MMGBSA results following IFD docking MD identified the top-performing compounds with scores of −84.0518, −75.2591, −71.8943, −84.2638, −56.3019, and −75.3873 kcal/mol, respectively. The MMGBSA results from QPLD docking MD identified the leading compounds with scores of −77.8486, −69.5773, −71.9171, N/A, −62.5716, and −66.8067 kcal/mol, respectively. In conclusion, based on the MMGBSA scores obtained using the three docking methods and the 100 ns MD simulations, and considering the combined evaluation of these methods, amprenavir, ferric derisomaltose, and bosutinib are proposed as the most promising candidates.